Enhanced Mechanical and Microstructural Properties of Portland Cement Composites Modified with Submicron Metakaolin - Yaoyu Wang; Jiye Li; Lihan Jiang; Lihua Zhao (Advances in Civil Engineering)
This work aims to study the influence of submicron metakaolin (SMK) on the mechanical strength, pore structure, and microstructural properties of hardened cement-based slurry (HCS). Portland cement was replaced by SMK at a proportion of 1, 3, 5, and 7 wt%. The compressive strength and flexural strength of the HCS samples were tested at a curing period of 3, 7, 14, and 28 days, and the pore structure of the specimens was analyzed by mercury intrusion porosimetry (MIP) at a curing period of 3 and 28 days. The microstructure characteristics of the hardened samples were investigated by scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDS). Thermogravimetric analysis (TGA) was also employed to analyze the change in the chemical composition of the HCS. The results showed that the SMK could accelerate the hydration rate of the cement and could improve the mechanical properties of the HCS; the compressive strength and flexural strength of the HCS samples were remarkably enhanced, compared to those of the plain cement, by 67 and 46%, respectively, at a curing period of 3 days and by 33 and 35%, respectively, at a curing period of 28 days. The SMK had a significant impact on the internal pore structure of the hardened samples, and the number of pores with a diameter of larger than 3000 nm significantly decreased. Because the hydration products filled the pores, the microstructure of the HCS was further refined and densified with the addition of SMK. Submicron metakaolin has a simple process and high activity, which can significantly improve the performance of the cement slurry. Therefore, submicron metakaolin has the potential for practical engineering applications.